2021
DOI: 10.1002/tox.23327
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HIF‐1α enhances the protective effect of mitophagy on steroid‐induced osteocytes apoptosis

Abstract: Glucocorticoid (GC; dexamethasone, DEX) ‐induced osteonecrosis of the femoral head (GIOFH) is a challenging orthopedic disease, and its underlying mechanism remains not clear. This study exposed murine long bone osteocyte‐Y4 (MLO‐Y4) cells to DEX below normoxic or hypoxic circumstances and found that cell autophagy have been reduced. At the same time, flow cytometry analysis showed increased apoptosis, which was more pronounced in hypoxic environments. Recent research also claimed that GC induces osteoporosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 68 publications
(69 reference statements)
0
24
0
Order By: Relevance
“…Targeting the mitophagy pathway in marrow mesenchymal stem cells may improve their survival capacity and chondrogenic differentiation for cell-based therapies in OA ( Sun et al, 2021 ). Overexpression of HIF-1α, through its downstream marker BNIP3, increases mitophagy induced by hypoxia and protects bone cells from apoptosis ( Xu et al, 2021 ). By enhancing BNIP3 expression, HIF-1α could alleviate hypoxia-induced apoptosis, senescence and matrix degradation in chondrocytes through mitophagy ( Hu et al, 2020b ).…”
Section: Pathogenesis Of Hif-1 In Osteoarthritismentioning
confidence: 99%
“…Targeting the mitophagy pathway in marrow mesenchymal stem cells may improve their survival capacity and chondrogenic differentiation for cell-based therapies in OA ( Sun et al, 2021 ). Overexpression of HIF-1α, through its downstream marker BNIP3, increases mitophagy induced by hypoxia and protects bone cells from apoptosis ( Xu et al, 2021 ). By enhancing BNIP3 expression, HIF-1α could alleviate hypoxia-induced apoptosis, senescence and matrix degradation in chondrocytes through mitophagy ( Hu et al, 2020b ).…”
Section: Pathogenesis Of Hif-1 In Osteoarthritismentioning
confidence: 99%
“…In addition, activation of autophagy by Beclin-1 overexpression induced osteoclast differentiation and conditional ablation of ATG7 and treatment with chloroquine, an autophagy inhibitor, ameliorated GC-induced bone loss via inhibiting osteoclastogenesis ( 18 ). Besides, recent studies indicated that GC can induce bone fragility and reduce osteocyte numbers by suppressing autophagy ( 19 ). Therefore, the maladjustment of autophagy may have a relationship with the occurrence and progression of GIOP, but related studies are still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1 α expression was decreased in the necrotic bone tissue of SANFH, and HIF-1 α compensatory expression was upregulated in early bone tissue under hypoxic or anoxic conditions. However, with the progression of the disease, the imbalance of energy metabolism in necrotic bone tissue was aggravated, and the expression levels of HIF-1 α , VEGF, HMOX1, and BNIP3 were decreased, resulting in the decreased differentiation and apoptosis of vascular endothelial cells [ 53 , 54 ]. (4) For the AGE-RAGE signaling pathway, under the action of GC, advanced glycation end products (AGE) and ROS accumulation occur in bone tissues and blood vessels of necrotic bone regions [ 55 ].…”
Section: Discussionmentioning
confidence: 99%